Elevated thiamine level is associated with activating interaction between HIF-1α and SLC19A3 in experimental myopic guinea pigs - Ma, Zhongyu; Hao, Jiawen; Yang, Zhaohui; Zhang, Miao; Zhang, Ruixue; Xin, Jizhao; Bao, Bo; Yin, Xuewei; Bi, Hongsheng; Guo, Dadong (Frontiers in Medicine, 2025)
BackgroundThe SLC19 gene family of solute carriers is a family of three transporter proteins with similar structures, of which SLC19A2 and SLC19A3 mediate thiamin transport; HIF is a transcriptionally active nuclear protein that is a key factor activated in hypoxic environments. Myopia is the most common eye disease that damages the visual health of adolescents, and currently, choroidal hypoxia is one of the prevailing doctrines of myopia, as well as the choroid as an ocular nutrient-supporting tissue, in which thiamine may play a role. This study aimed to investigate the process of thiamine changes in choroidal tissue of guinea pigs with negative lens-induced myopia (LIM).MethodsThe right eyes of guinea pigs in the LIM group wore −6.0D lenses to model experimental myopia. Biological measurements of ocular parameters and choroidal thickness (ChT) were measured after 2, 4, and 6 weeks of modeling. Real-time fluorescence quantitative PCR and Western blot were used to detect the expression of SLC19A2, SLC19A3, and HIF-1α in the choroidal tissues of each guinea pig, ELISA was used to detect the changes of thiamine content in the choroidal tissues, and HE staining was used to observe the morphological changes of the choroidal tissues. Immunofluorescence and immunohistochemistry detected the expression of SLC19A3 and SLC19A3 in choroidal tissues at different modeling times, and protein immunoprecipitation and molecular docking verified the interactions between HIF-1α and SLC19A3.ResultsCompared with the normal control (NC) group, the LIM group guinea pigs showed a significant increase in axial length and decrease in refractive error, as well as a thinning of choroidal thickness and loosening of tissue structure. In addition, the expression of SLC19A3 was higher than that of the NC group at 2 and 4 weeks, SLC19A2 was higher than that of the NC group at 4 weeks, and HIF-1α was higher than that of the NC group at 2, 4, and 6 weeks. Moreover, protein immunoprecipitation revealed a reciprocal relationship between HIF-1α and SLC19A3, and molecular docking showed their sites of action.ConclusionThe current study suggests that the choroidal tissue in myopic eyes is hypoxic and has metabolic abnormalities. Thiamine, a critical molecule for metabolism, may play a significant role in the process. Our findings indicate that changes in thiamine levels within the choroidal tissue are associated with elevated choroidal HIF-1α and activation of SLC19A3, which enhances thiamine transport. This suggests an adaptive regulatory mechanism for thiamine in myopia. Our research highlights thiamine as a potential target for pharmacological inhibitors and could lead to new insights into the study of the molecular mechanisms of myopia, as well as novel strategies for treating the disease.